IMPROVING PATIENT SAFETY THROUGH SOCIALIZATION OF FALL RISK ASSESSMENT TOOLS: COMMUNITY SERVICE ACTIVITIES WITH HEALTH WORKERS - Kulsum, Ummi; Hasinuddin, M; Soliha, Soliha (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: The socialization of the development of fall risk assessment tools is essential as it is part of the hospital patient safety service system that can provide a sense of security to patients in receiving healthcare services in the hospital. The purpose of this program is to improve nurses' knowledge, facilitate nurses in conducting fall risk assessments, and optimize the time in assessing fall risks. Methods: This community service was conducted for 20 healthcare workers at RSU Anna Medika Madura. The method used involved interactive learning through lectures, demonstrations/simulations, and discussions. The instrument used was an adaptation of the Fall Risk Assessment Tool. Pre-test and post-test questionnaires were used to measure participants' knowledge levels. The data were analyzed using descriptive statistics and a one-sample t-test. Results: The demographic characteristics of the participants were dominated by ages 24 (20%) and 28 (20%), with half of the respondents being female (50.0%) and half male (50.0%). Almost all respondents worked as nurses (95.0%), and the majority of respondents were from the inpatient unit (40.0%). The results of the one-sample t-test showed a p-value of 0.000, indicating a significant difference in healthcare workers' knowledge before and after being given a socialization program on the concept of patient safety and the development of a fall risk assessment instrument for patients. Conclusion: Engaging in interactive learning through presentation methods significantly increases knowledge about patient safety concepts and the development of fall risk assessment instruments for patients. Knowledge about developing fall risk assessment tools should be updated regularly.